Hemangiopericytoma - The need for a protocol-based treatment plan - Murugesan Krishnan; K Sree Kumar; T Sowmiya (Wolters Kluwer Medknow Publications, 2011)
Hemangiopericytoma is a vascular tumor which comprises only 1% of all vascular tumors. The frequency of occurrence in the head and neck accounts for about 16-33% of all hemangiopericytomas. In this paper we discuss the surgical management, the difficulties in decision-making and treatment-planning in a case of a maxillary tumor in a five-year-old boy with a two-year follow-up. A five-year-old boy presented with a large unilateral maxillary tumor with nasal obstruction. Computed tomography revealed a heterogeneous mass completely occupying the right maxillary sinus and displacing the lateral wall of the nose and nasal septum. The lesion was diagnosed as hemangiopericytoma after histopathological confirmation. The option of surgical resection (total maxillectomy) was carried out after evaluating the available literature. Various treatment modalities like surgery, chemotherapy and radiotherapy were taken into consideration as the tumor has an aggressive nature. Due to the inadequate literature on definitive treatment options for these types of tumors, there was difficulty in arriving at a protocol-based treatment plan.